SOCIAL CONTRACT IMPLEMENTATION IN ELECTIONS IN INDONESIA - Agus Fatah Hidayat; Tatang Parjaman; Tasuku Maruoko; Agus Dedi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The social contract in a political perspective is a human agreement to concentrate power in the hands of a person or an assembly that has leadership rights. At the implementation level, social contracts can be interpreted as agreements and agreements between individuals to give up their rights and then submit to leaders through the electoral process. The research method used is descriptive method with a qualitative approach. With this method the researcher tries to describe, analyze, and build meaning about the implementation of social contracts in elections in Indonesia. The results of the study explain that the social contract in elections must guarantee the trust given by voters to those they choose. Elections are a general will that is manifested in the form of civil society taking part in creating a government that is in accordance with the will of the people so that it is a manifestation of a "social contract" and becomes a political necessity based on the mutual agreement of the Indonesian people.